Field notes contributed by Robert Gruenewald with a reply form letter from Thomas H. Kent, fall 1998 - Kent, Thomas H. (Thomas Hugh), 1934-et al; Gruenewald, Robertet al (1998)
Fall report of birds found in O'Brien County contributed by Robert Gruenewald. Also included is a form letter from Thomas H. Kent to Gruenewald regarding a request for more information and answers to several inquiries about bird names. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1998. Epson - sheet feed